O PARTO NA VOZ DA PARTURIENTE - Grandi, Carine Baldicera de (2017)
Introduction: the experience of gestation and birth are important moments in the life of a woman, this event is part of the reproductive life and goes far beyond its physiological aspects. Health work practices can include several technologies, among them, videos, educational video can be an example of an instrument used as a technological didactic resource. Overall objective: to elucidate the experience of childbirth through the report of women who have recently experienced the birth of a child. Specific objectives: to give voice to women about their birth experiences; build and validate a video with reports of positive and negative experiences of childbirth. Methodologi: In order to meet the first specific objective, a qualitative descriptive exploratory study was carried out between April and August 2017 with eleven women who had a normal or cesarean birth in the central region of Rio Grande do Sul. The second specific objective was of a methodological research in the month of November of 2017 with twelve specialized judges in the maternal and child area. Results: of the research data organized and codified by the content analysis resulted in three thematic axes: Childbirth as experience; Labor pains; Protective factors and measures of comfort. From the methodological research, we obtained a return of twelve instrument of evaluation of the expert judges. The Likert Scale was adapted. The video was considered valid. Thus, a documentary video validated by expert judges of the area will be made available as a product of this research process to subsidize discussions about types of birth among professionals and academics. Final considerations: The initial goal was achieved, the documentary video, elucidating the report of women about their experience of delivery, was validated, after the analysis of 12 expert judges, was obtained 90% agreement. The empowerment of pregnant women is perceived in the direction of a conscious and non-fear-based decision-making, favoring experiences of dialogue between women and professionals.